Alternative Splicing in Tumorigenesis and Cancer Therapy - Huiping Chen; Jingqun Tang; Juanjuan Xiang (Biomolecules)
Alternative splicing (AS) is a pivotal post-transcriptional mechanism that expands the functional diversity of the proteome by enabling a single gene to generate multiple mRNA and protein isoforms. This process, which involves the differential inclusion or exclusion of exons and introns, is tightly regulated by splicing factors (SFs), such as serine/arginine-rich proteins (SRs), heterogeneous nuclear ribonucleoproteins (hnRNPs), and RNA-binding motif (RBM) proteins. These factors recognize specific sequences, including 5′ and 3′ splice sites and branch points, to ensure precise splicing. While AS is essential for normal cellular function, its dysregulation is increasingly implicated in cancer pathogenesis. Aberrant splicing can lead to the production of oncogenic isoforms that promote tumorigenesis, metastasis, and resistance to therapy. Furthermore, such abnormalities can cause the loss of tumor-suppressing activity, thereby contributing to cancer development. Importantly, abnormal AS events can generate neoantigens, which are presented on tumor cell surfaces via major histocompatibility complex (MHC) molecules, suggesting novel targets for cancer immunotherapy. Additionally, splice-switching oligonucleotides (SSOs) have shown promise as therapeutic agents because they modulate splicing patterns to restore normal gene function or induce tumor-suppressive isoforms. This review explores the mechanisms of AS dysregulation in cancer, its role in tumor progression, and its potential as a therapeutic target. We also discuss innovative technologies, such as high-throughput sequencing and computational approaches, that are revolutionizing the study of AS in cancer. Finally, we address the challenges and future prospects of targeting AS for personalized cancer therapies, emphasizing its potential in precision medicine.